The Shift and Form of Censorship. Scientific and Practical Conference - fakultetas, Komunikacijos (Žurnalistikos tyrimai, 2017)
Vilnius University, 2017 05 04: Vilnius University, White Hall and President A. Smetona ManorThe international scientific-practical conference “The Shift and Form of Censorship”, held on May 4–5, 2017, explored how censorship is evolving and impacting media, society, and political discourse. The first day in Vilnius focused on journalism in Russia and Lithuania, including the challenges facing investigative journalism. The second day, held at President Antanas Smetona’s manor, featured academic presentations on freedom of expression, latent forms of censorship, media institutional frameworks, and historical insights. Speakers examined contemporary censorship challenges—from the influence of language on thought to unofficial media control in Russia—and encouraged fresh perspectives on media freedom.
Keywords: Censorship; Media; Freedom of expression; Informal control; Journalism